Göbekli Tepe, Türkei - Dietrich, Oliver; Köksal-Schmidt, Çiğdem; Notroff, Jens; Schmidt, Klaus (e-Forschungsberichte des DAI, 2023)
A few kilometres to the northeast of Şanlıurfa in southeastern Turkey the tell of Göbekli Tepe is situated. The immense ruin hill formed by the debris of monumental constructions dating back into the 10th and 9th millennium BC (the Pre-Pottery Neolithic) has been excavated systematically since 1995. The last two excavation campaigns were preliminary focussed on work to erect permanent shelter structures to preserve the site.